The Empowerment Strategy On Fishermen Community In Pondok Kelapa Village, Pondok Kelapa Subdistrict, Bengkulu Tengah District, Bengkulu Province - Azuwandri Azuwandri; Gustini Gustini (Penerbit Jurnal Indonesia, 2024)
The purposes of this study is to identify factors that affect the emerging of poverty and to formulate policy strategies in empowering fishermen communities in the village of Pondok Kelapa, Pondok Kelapa subdistrict, Bengkulu Tengah regency. This research was case study using descriptive methods. The number of sample (respondent) of the study was 30 (thirty) individuals, 5 (five) were from the regional work units of Bengkulu Tengah regency and 25 (twenty five) consisted of fishermen, traders (middlemen), and the fisherman's wives (traders). The methods of analysis used in this study were: (1) descriptive analysis used to describe the causes of poverty happening to the people in the study sites, and (2) SWOT analysis used to formulate strategies on empowerment of fishermen communities at the sites. Results of the study show that the identified social aspects were: the low education of respondents, the large number of family members that must be defrayed, and the unpredictable natural factors. In economic aspect, it was found that fishermen were affected by the fish catches and inadequate income. Whereas in the institutional aspect, it was found that respondents were enthusiastic to join the group, but the problem were as the knowledge and guidance was low. From the SWOT analysis, it was obtained five strategies to empower the fishermen community, namely: (1). Development of fisheries technology, (2). Development of appropriate technologies mastery, (3). Development of fisheries diversification, (4). Building of facilities and infrastructures for fishery business, and (5). Institutional reinforcement of coastal communities.